Construction and Application of Standardized Postoperative Pain-Management Procedure for Patients With Perianal Abscess: A Retrospective Study - Wang, Xiu-Mei; Jiang, Wei-Lian; Ma, Li-Fang; Guo, Yue; Cui, Li-Ping; Niu, Yan-Bin (Frontiers in Surgery, 2022)
Objective: The present study explored the construction and application of a standardized postoperative pain-management procedure for patients with perianal abscess. Methods: Two study groups (the observation group and the intervention group) were established retrospectively. The observation group comprised 46 patients with perianal abscess who enrolled in this study between June 2019 and June 2020. The intervention group comprised 48 patients who enrolled in the study between July 2020 and July 2021. All patients were enrolled using the convenience sampling method. A pain-management team was established, and standardized procedure management was implemented in the intervention group, while routine pain management was implemented in the observation group. Indices related to the patients’ postoperative pain-control satisfaction and rehabilitation were compared between the two groups. Results: The patients’ pain-control satisfaction, wound edema score, edema disappearance time, urinary retention, and defecation difficulty following intervention were better in the intervention group than in the observation group, and the differences were statistically significant (P < 0.05 for all). Conclusion: The implementation of the standardized postoperative pain-management procedure in patients with perianal abscess can effectively improve the patient’s level of pain and satisfaction and promote rehabilitation.